Uncovering Unique Green Algae and Cyanobacteria Isolated from Biocrusts in Highly Saline Potash Tailing Pile Habitats, Using an Integrative Approach - Sommer, Veronika (Microorganisms, 2020)
Potash tailing piles caused by fertilizer production shape their surroundings because of the associated salt impact. A previous study in these environments addressed the functional community “biocrust” comprising various micro- and macro-organisms inhabiting the soil surface. In that previous study, biocrust microalgae and cyanobacteria were isolated and morphologically identified amongst an ecological discussion. However, morphological species identification maybe is difficult because of phenotypic plasticity, which might lead to misidentifications. The present study revisited the earlier species list using an integrative approach, including molecular methods. Seventy-six strains were sequenced using the markers small subunit (SSU) rRNA gene and internal transcribed spacer (ITS). Phylogenetic analyses confirmed some morphologically identified species. However, several other strains could only be identified at the genus level. This indicates a high proportion of possibly unknown taxa, underlined by the low congruence of the previous morphological identifications to our results. In general, the integrative approach resulted in more precise species identifications and should be considered as an extension of the previous morphological species list. The majority of taxa found were common in saline habitats, whereas some were more likely to occur in nonsaline environments. Consequently, biocrusts in saline environments of potash tailing piles contain unique microalgae and cyanobacteria that will possibly reveal several new taxa in more detailed future studies and, hence, provide new data on the biodiversity, as well as new candidates for applied research.